Health Care in World Cities : New York, Paris, and London. - Gusmano, Michael K.; Rodwin, Victor G.; Weisz, Daniel (Baltimore : Johns Hopkins University Press, 2010)
In providing empirical comparisons of access to care in these three health systems, the authors refute inaccurate claims about health care outside of the United States.
Intro -- Contents -- Preface -- Acknowledgments -- 1. A New Approach to Comparing Health Systems -- 2. Comparable Cities within Contrasting Health Systems -- 3. Overall Performance of the Health System: Avoidable Mortality -- 4. Access to Primary Care: Avoidable Hospital Conditions -- 5. Access to Specialty Care: The Treatment of Heart Disease -- 6. Conclusions -- Appendix: Data and Methods -- References -- Index -- A -- B -- C -- D -- E -- F -- G -- H -- I -- J -- K -- L -- M -- N -- O -- P -- Q -- R -- S -- T -- U -- V -- W.
Description based on publisher supplied metadata and other sources.
Electronic reproduction. Ann Arbor, Michigan : ProQuest Ebook Central, 2024. Available via World Wide Web. Access may be limited to ProQuest Ebook Central affiliated libraries.
Keywords: Health status indicators-New York (State)-New York; Health status indicators-France-Paris.; Health status indicators-England-London.; Urban health; Electronic books